Penyuluhan Disentri Kepada Siswa/i SMA Santo Yoseph - Hutasoit, Eka Samuel P.; Simanjuntak, Maestro Bina Utama; Zebua, Ribka Febrianti; Sihite, Rubintang; Siregar, Resisca Mariani (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Community Service is an activity that must be carried out compulsorily by students in order to fulfill the Tridharma of Higher Education, which includes providing material in the form of health education to the surrounding community. This activity takes the topic of Dysentery, where this topic really needs to be shared with the public considering that currently the death rate caused by Dysentery cases has reached 1.1 million per year globally, with the most cases occurring in developing countries, one of which is Indonesia. The aim of this service activity is to provide knowledge and knowledge about Dysentery starting from prevention and initial treatment. This activity was held on February 3 2024 at Santo Yoseph High School, Medan City with a total of 20 students as participants. It is hoped that the results of this service activity will provide good results, resulting in a clean and healthy lifestyle to reduce the risk of getting dysentery in order to create a healthy and intelligent generation.